IMPLEMENTASI E-PROCUREMENT LOGISTIK SEBAGAI EFISIENSI ANGGARAN PADA PEMILIHAN KEPALA DAERAH KABUPATEN PESAWARAN TAHUN 2020 - Feni Rosalia; Tabah Maryanah; irawan hartono (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2022)
In order to reduce the huge pilkada costs, the implementation of E-procurement in the procurement of election logistics will be an important first step. E-procurement is a development from conventional procurement to E-procurement where the procurement process is carried out electronically via the web/internet and uses communication and information technology facilities such as public auctions, prequalification and electronic procurement using website-based modules. This change is projected to produce a more effective, efficient, transparent and accountable government. The purpose of this study was to determine whether the implementation of E-procurement general election logistics procurement in PesawaranRegency resulted in budget efficiency. The research method used is descriptive research with qualitative and quantitative data analysis. The data used were obtained through observation, interviews and documentation. The results of this study indicate thatthe implementation of E-procurement in the process of procurement of election logistics goods at the KPU secretariat of Pesawaran Regency causes the efficiency of the regional election budget in accordance with the objectives of the implementation of E-procurement. This can be seen by the large difference between the available budget and its realization. The application of E-procurement can also be applied to the implementation of the simultaneous General Election in 2024 so that much greater budget efficiency can be carried out